Strategi Komunikasi Yayasan Muslim Youth Club dalam Pembinaan Ibadah pada Remaja di Kabupaten Batu Bara - Yulia Nurul Putri; Rubino Rubino; Andini Nur Bahri (Maktabatun: Jurnal Perpustakaan dan Informasi, 2023)
This study aims to determine the communication strategy of the Muslim Youth Club Foundation in fostering worship for adolescents in Batu Bara District. This research was conducted at Al Izzah Integrated Islamic Private High School, Aras Village, Air Putih District, Batu Bara Regency, North Sumatra. The method used in this study is a qualitative research method, a method carried out by looking at phenomena that occur or field conditions with data collection techniques. data and from research informants. There were 6 informants consisting of the chairman of the foundation, the secretary, the HRD department, the women's department and two fostered youths. Data collection techniques were carried out through interviews and documentation. The results of the research found as follows: 1) The communication strategy used by the Muslim Youth Club Foundation in fostering worship for adolescents in Batu Bara Regency consists of several steps: first, determining the audience by taking into account the frame of reference and the situation and the conditions of the audience, compiling the contents of the message according to the conditions of the audience, determining methods including informative methods, question and answer methods and persuasive methods, selecting communication media including modules and the Koran, establishing the role of the communicator namely as role models and conducting evaluations. 2) There are several obstacles in developing communication strategies for fostering worship for adolescents in Batu Bara Regency, namely: psychological barriers, originating from the psychological condition of the communicant who feels worried and anxious, semantic barriers originating from differences in the language commonly used, mechanical barriers due to inadequate media inadequate and ecological barriers due to clamor and noise